Contribution of Mui-Dsn Fatwa on Operational Products of Mudharabah-Wadi’ah Bank Sharia Indonesia - Hadi, Muhammad (Li Falah: Journal of Islamic Economics and Business, 2022)
Fatwa of the Indonesian Ulema Council and the Indonesian Sharia Council recommend non-interest-based banking institutions that are built on the basis of the Qur’an and Hadith. Along with the issuance of the fatwa above, Islamic banking continues to experience rapid growth, even with the merging of Bank Syariah Mandiri, BNI Syariah, and B.R.I. Syariah into one umbrella of Bank Syariah Indonesia (B.S.I.). More complete than other banks in Kendari. The purpose of Islamic banks is not only to function as funding and loan services. Currently, Islamic banks are expanding to develop other financial services, including gold pawning, Western Union, hajj bailouts and others. This article uses qualitative methods through observation, research, and data collection). This method can be used to understand the role of the fatwa on mudharabah-wadi’ah contract products at B.S.I., which is not yet known. To fully understand the role of the MUI-DSN fatwa, the researcher uses the maqashid al-Syari’ah al-Syatibi approach, which is expressed in dharuriyat, which includes khifd al-dien, aql, nafs, aql, and mal. From the data collected, the findings in this article have not shown a significant effect since the merger of the three B.S.M., BNI sharia, and B.R.I. sharia transformed into B.S.I., which has not had any progress for customers. To prove that “The role of the MUI-DSN fatwa in the operationalization of mudharabah-wadi’ah contract products at the B.S.I. Kendari bank” illustrated the existence of different contract implementation regulations in each product integrated with customers, for example, wadi’ah contracts for safekeeping, mudharabah for financing buying or building a house, musharaka for financing business development, and others. This research can later become an additional academic reference, especially for the Faculty of Economics and Islamic Business IAIN Kendari, because it seeks to explain the financing model through the contract system carried out by Bank BNI Syariah Kendari City.